Tail fell syndrome impacts intestinal microbiota in porcupinefish (Diodon hystrix) - Zhou, Lei; Jia, Xianze; Liang, Kaishan; Zuo, Xiaoling; Huang, Fengqi; Duan, Xuzhuo; Li, Zongyang; Sang, Shilei; Wang, Qing (Frontiers in Marine Science, 2023)
Introduction Frequent disease outbreaks seriously affect porcupinefish (Diodon hystrix), which is a new aquaculture breed in China. Recently, a novel disease, termed tail fell syndrome (TFS) was increasingly observed in fish stocks, resulting in stalk ulceration, tail loss, ascites and white feces in the intestine. Intestinal microbiota homeostasis is crucial to host health because it influences host and environmental factors, and responds to various internal and external stimuli. However, changes in intestinal microbiota induced by TFS are yet to be elucidated. Methods In the present study, we analyzed and compared the intestinal microbiota of normal D. hystrix with TFS fish. Results Though microbiota richness and diversity were not affected by TFS, deviations in diversity indices increased and taxa distribution evenness decreased, suggesting TFS lowered microbiota community stability in D. hystrix. Furthermore, at the genus level, Brevibacterium, Mesorhizobium, Ochrobactrum, Ralstonia, Anaerococcus, and Alistipes abundances were significantly increased in TFS D. hystrix, plus, we observed significant decreases in Halomonas, Prevotellaceae_NK3B31_group, and Psychrobacter. Functional comparison predictions between normal and TFS D. hystrix revealed significantly altered pathways were mainly associated with metabolism (biotin metabolism, steroid hormone biosynthesis, flavonoid biosynthesis, biosynthesis of type II polyketide products, and steroid biosynthesis). Overall, the results revealed that TFS impacted intestinal microbiota composition and function in D. hystrix, which should expand our knowledge on diseases associated with porcupine pufferfish aquaculture.